Towards criteria and symptoms of constipation in people with severe or profound intellectual and multiple disabilities: A Delphi study - A. Waninge; A.A.J. Van der Putten; M.C. Wagenaar; C.P. Van der Schans (Heliyon, 2023)
Background: Chronic constipation is common in people with intellectual disabilities, and seems to be highly prevalent in people with severe or profound intellectual and multiple disabilities (SPIMD). However, there is no current widely accepted definition for the constipation experienced by these individuals. Aim: This Delphi study aims to compile a list of operationalized criteria and symptoms of constipation in people with SPIMD based on practical experiences of and consensus between experts supporting them. Methods: A two-round Delphi study with an intermediate evaluation and analyses was conducted. Parents and relatives of persons with SPIMD and support professionals were included. The panel answered statements and open questions about symptoms and criteria of constipation. They were also requested to provide their opinion about classifying criteria and symptoms into domains. Answers to statements were analysed separately after both rounds with regard to consensus rate and displayed qualitatively; answers to open questions were analysed deductively. Results: In the first Delphi round (n = 47), consensus was achieved on criteria within the domains 'Defecation’ and 'Physical features', that were assigned to broader categories. Symptoms retrieved within the domain ‘Behavioural/Emotional’ were brought back to the panel as statements. After the second Delphi round (n = 38), consensus was reached on questions about domains, and for eight criteria (domain ‘Defecation’ n = 5; domain ‘Physical features n = 3). Within the domain ‘Behavioural/Emotional’, consensus was achieved for five symptoms. Criteria and symptoms with consensus >70% were considered ‘generic’ and <70% as ‘personal’. Symptoms mentioned in the text boxes were used to operationalize categories. Discussion and conclusion: It was possible to compile a list of generic criteria related to the domains ‘Defecation’ (n = 5) and ‘Physical features’ (n = 3) supplemented with generic symptoms related to the domain ‘Behavioural/Emotional’ (n = 5). We propose using both generic as well as personal criteria and symptoms resulting in a personal profile for an individual with SPIMD. Based on the current results, we recommend follow-up research to develop a screening tool to be used by relatives and professional caregivers, and a definition of constipation. This may support reciprocal collaboration and lead to timely identification of constipation in people with SPIMD.